Damage Analysis and Repair in Overhaul Motor Pump Water Treatment Plant (WTP) PT Petrokimia Gresik Sub Babat Lamongan Plant using FMEA Method - Dzaky Budhi Pratama; Pressa P Perdana Surya (Jurusan Teknik Elektro Universitas Trunojoyo Madura, 2025)
In the Water Treatment Plant (WTP) industry, motor pump maintenance is very important to maintain system performance. PT Petrokimia Gresik Sub Babat Lamongan Plant faces challenges in maintaining motor pumps that are crucial to their operations. To improve maintenance and reduce failures, a damage analysis was conducted using the Failure Mode and Effect Analysis (FMEA) method. This study aims to evaluate the potential for motor pump damage by identifying various failure modes, their impacts, and appropriate repair steps. FMEA is used to assess the risk of each failure mode, focusing on early detection and repair recommendations to improve motor pump reliability and efficiency. From 430 data analyzed, several main failure modes were found: lights out (27.6%), motor cable broken (19.6%), Motor fault (17.3%), crane jammed (9.2%), and pump jammed (6.9%). Other damages such as broken light switches, oil leaks, and abnormal sounds have a smaller percentage. The average Severity value of 6.75, Occurrence 4.5, Detection 5, and the highest Risk Priority Number (RPN) value of 252 were found in Motor Fault mode, indicating that Motor fault is the biggest risk that must be the main priority in handling and repair.